KOMUNIKASI MEREK, KUALITAS LAYANAN DAN KEPERCAYAAN MEREK DALAM MEMBANGUN LOYALITAS MEREK (STUDI KASUS PEMBELIAN SEPEDA MOTOR YAMAHA NMAX DI KABUPATEN PESISIR SELATAN) - Sridela Amanda Putri; Lola Fitria Sari; Willy Nofranita (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The brand is an intangible asset owned by a company. This study aims to determine the effect of brand communication (X1), service quality (X2), and brand trust (X3) in building brand loyalty (Y) in case studies of purchasing Yamaha NMax motorbikes in Pesisir Selatan. The number of samples in this study was 220 respondents who bought Yamaha Nmax motorcycles on the South Coast. The observed data were processed using the Structural Equation Modeling (SEM) method with the Stata 17 program. The partial test results in this study showed that brand communication effected service quality. Brand communication affects brand trust. Brand communication affects brand loyalty. Service quality affects brand trust. Service quality affects brand loyalty. And brand trust also shows a positive and significant value on loyalty. These results prove that brand communication and service quality affect brand loyalty through brand trust. When brand communication activities and service quality succeed in influencing customer trust they become loyal to a brand that makes customers loyal to that brand.Keywords: Brand Communication, Service Quality, Brand Trust, Brand Loyalty